ANALISIS PENERAPAN KURIKULUM MERDEKA MATERI POLA HIDUP BERGOTONG ROYONG MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 1 BOLOGARANG - Tuti Alawiyah; Ika Ari Pratiwi; Wawan Shokib Rondli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe how the implementation and inhibiting factors in the implementation of the Merdeka Curriculum implemented by teachers on the material of the Mutual Cooperation Lifestyle in class IV at SDN 1 Bologarang Grobogan in 2023/2024. This study uses a qualitative approach with a narrative type. Data collection techniques with interviews, observation and documentation to test the validity of the data are credibility, transferability, dependability, and confirmability. Meanwhile, the data analysis technique used consists of three stages, namely the data reduction stage, the data presentation stage and the conclusion/verification stage. The implementation of the Merdeka Curriculum on the material of the Mutual Cooperation Lifestyle in class IV of SDN 1 Bologarang Grobogan has followed the stages according to the concept of the Merdeka Curriculum. In planning, teachers make comprehensive preparations, such as MGMP, understanding curriculum characteristics, analyzing Learning Outcomes, and compiling Learning Objectives and Teaching Modules. In implementation, learning applies a problem-based learning approach and community-based learning. In the evaluation, most students got high scores because they understood and could follow the lesson well, and were able to give examples of mutual cooperation in schools and communities. However, there are still students who tend to be passive and less involved in the practice of mutual cooperation. The inhibiting factors in the implementation of the independent curriculum in this material are: (a) lack of student interest, (b) adaptation to the new curriculum model, and (c) lack of training and socialization of professional development for teachers.